Augustinus and Kant – Two Founders of Modern Thinking - Bobko, Aleksander (Studia z Historii Filozofii, 2019)
A number of factors have contributed to spectacular technological progress in recent times, one of the most important of which, in my opinion, was the development of philosophical ideas, especially the concept of the autonomous subject. The key moment for theoretical foundations of that concept seems to be the publication of The Critique of Pure Reason by Immanuel Kant. In my paper, I would like to show that the sources of the concept of the autonomous subject developed by Kant can be found in the philosophy of Saint Augustine, especially in his treatise “On the Holy Trinity”. I will try to underline the specific analogy between “the life of the soul” described by Augustine and Kant’s account of “pure reason”; to emphasize the remarkable parallel between the two works: “The Critique of Pure Reason” and “On the Holy Trinity”. Drawing such historical parallels is dangerous and may arouse doubts about one’s methodology. The two works are separated by a span of nearly fourteen centuries, two giants of philosophy who were their authors apparently had nothing in common. In spite of that, I will support the hypothesis that Kant’s theory is a philosophical development of intuitions formulated, in a metaphorical way, by Saint Augustine.